2019
DOI: 10.1002/anie.201814262
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructures Composed of N‐Doped Carbon Nanotubes Encapsulating Cobalt and β‐Mo2C Nanoparticles as Bifunctional Electrodes for Water Splitting

Abstract: Herein, we demonstrate the use of heterostructures comprised of Co/β‐Mo2C@N‐CNT hybrids for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an alkaline electrolyte. The Co can not only create a well‐defined heterointerface with β‐Mo2C but also overcomes the poor OER activity of β‐Mo2C, thus leading to enhanced electrocatalytic activity for HER and OER. DFT calculations further proved that cooperation between the N‐CNTs, Co, and β‐Mo2C results in lower energy barriers of intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
292
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 694 publications
(307 citation statements)
references
References 56 publications
5
292
0
1
Order By: Relevance
“…Besides, the XPS spectra (Figure S15a) show that after stability test the valence state of Ni was not be changed both in anode and cathode sides. Interestingly, the Ni in Ni/MoN@NCNT/CC was not be oxidized and remained unchanged in the OER process, which could be ascribed to the protection of carbon layer, consistent with some reported OER electrocatalysts, such as Co@NCF, FeNi@NC and Co/β‐Mo 2 C@N‐CNTs, Ni/Mo 2 C‐PC . However, the MoN was not very stable and oxidized into Mo 6+ species in the anode side (Figure S15b), which can enhance OER performance of electrocatalysts .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Besides, the XPS spectra (Figure S15a) show that after stability test the valence state of Ni was not be changed both in anode and cathode sides. Interestingly, the Ni in Ni/MoN@NCNT/CC was not be oxidized and remained unchanged in the OER process, which could be ascribed to the protection of carbon layer, consistent with some reported OER electrocatalysts, such as Co@NCF, FeNi@NC and Co/β‐Mo 2 C@N‐CNTs, Ni/Mo 2 C‐PC . However, the MoN was not very stable and oxidized into Mo 6+ species in the anode side (Figure S15b), which can enhance OER performance of electrocatalysts .…”
Section: Resultssupporting
confidence: 89%
“…More TEM images are shown in Figure S7, further confirming nanoparticles were encapsulated in NCNT. Besides, many literatures reported that nanoparticles were encapsulated in carbon nanotubes, which are also confirmed by TEM images. Figure and S7 present similar results with those TEM images, so it is convincing that nanoparticles were encapsulated in NCNT and not anchored to their surface.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In recent years, there has been an ever-growing interest in the development of efficient, earth-abundant and inexpensive Pt-free electrocatalysts with long-term stability.O ft hese, molybdenum (Mo)-based compounds including Mo 2 C, [17][18][19] MoS 2 [20,21] and MoSe 2 [22,23] nanostructured materials have demonstrated remarkable HER performance [24,25] and have proven to be alternatives for Pt-based electrocatalysiso ft he HER. In particular, MoSe 2 represents ap romising non-noble-metalbased electrocatalyst and has one of the best-known HER performance in media.…”
Section: Introductionmentioning
confidence: 99%